P‐58: Highly Stable Organic Thin‐Film Transistor array Fabricated on Gorilla Glass Substrates using Direct Photolithography. Issue 1 (June 2015) - YingtaoXie,; Ouyang, Shihong; Wang, Dongping; Zhu, Dalong; Xu, Xin; Tan, Te; Lee, Wen‐Ya; Bao, Zhenan; Matthews, James R.; Niu, Weijun; Simonton, Kristi L.; Myers, Timothy E.; et al.
Abstract : Photolithography is applied to pattern PTDC16DPPTDC17FT4‐based organic thin‐film transistors (OTFTs) array on the ionexchanged NAS glass substrate with pattern features down to 10 µm. Result demonstrates high stability and excellent uniformity of bottom contact OTFT devices incorporated with a photopatternable polymer gate insulator over 2" × 2" Gorilla glass substrates.